Экспериментальные исследования прямолинейного неустановившегося движения гусеничного трактора с объемным гидроприводом - Самородов, Вадим Борисович; Мандрыка, Владимир Ростиславович (НТУ "ХПИ", 2017)
Экспериментально проведены сравнительные испытания динамической нагруженности при разгоне гусеничных тракторов с механической трансмиссией и с объемным гидроприводом. Установлено, что снижение динамической нагруженности в зависимости от пахоты или транспортных работ для трактора с объемным гидроприводом в процессе разгона уменьшается от 1,6 до 2,1 раза соответственно по сравнению с аналогичным трактором с механической трансмиссией.

To determine the dynamic loading of the transmission during the acceleration, experimental studies of caterpillar tractors wi th a pulling force of 30 KN were carried out. The serial T-150 tractor with a mechanical transmission and the T-150E tractor were investigated, in which the serial gearbox and cardan gears were replaced by two full-flow volume hydraulic drives (GVP) with adjustable pumps and unregulated hydraulic motors providing independent torque transmission to the driving wheels of the left and starboard sides . It was found that the decrease in dynamic loading dur ing the acceleration for the tractor with UGP decreases from 1.6 to 2.1 times, depending on the plowing or transport operations, respectively, compared with a similar tractor with a mechanical transmission.
Experimental studies of rectilinear unsteady movement of a caterpillar tractor with a volume hydraulic drive
Keywords: нагруженность динамическая; разгон; скорость вращения; вал двигателя; скорость перемещения; сервоустройства; dynamic loading; acceleration; volumetric hydraulic drive; engine shaft rotation speed; speed of moving; servo devices